2014
DOI: 10.1371/journal.pone.0095478
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Complement C3 and C3aR Expression in Subcutaneous Adipose Tissue in Obese Women

Abstract: BackgroundThe central component of the complement system, C3, is associated with obesity, metabolic syndrome and cardiovascular disease however the underlying reasons are unknown. In the present study we evaluated gene expression of C3, the cleavage product C3a/C3adesArg and its cognate receptor C3aR in subcutaneous and omental adipose tissue in women.MethodsWomen (n = 140, 21–69 years, BMI 19.5–79 kg/m2) were evaluated for anthropometric and blood parameters, and adipose tissue gene expression.ResultsSubjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(75 reference statements)
2
7
0
Order By: Relevance
“…In the former, the mRNA was detected mostly in the heart and the lung, and to a lesser extent in the kidney, liver, skeletal muscles, and adipose tissue, but not in the brain and the spleen (10,11). In humans, C3AR1 mRNA was found in large amounts in lung, spleen, small intestine, peripheral blood leukocytes, s.c. adipose tissue, and at low levels in the kidney and heart but not in the brain (5,6,71). Our data obtained with the tdTomato-C3aR knock-in mouse confirmed the presence of C3aR expression in the lung and VAT.…”
Section: Discussionsupporting
confidence: 79%
“…In the former, the mRNA was detected mostly in the heart and the lung, and to a lesser extent in the kidney, liver, skeletal muscles, and adipose tissue, but not in the brain and the spleen (10,11). In humans, C3AR1 mRNA was found in large amounts in lung, spleen, small intestine, peripheral blood leukocytes, s.c. adipose tissue, and at low levels in the kidney and heart but not in the brain (5,6,71). Our data obtained with the tdTomato-C3aR knock-in mouse confirmed the presence of C3aR expression in the lung and VAT.…”
Section: Discussionsupporting
confidence: 79%
“…It is fascinating that the C3 expression decreases with obesity in the present study given that C3 mRNA expression levels typically positively correlated with obesity. Nevertheless, this finding is in agreement with recent discovery by Gupta et al [ 30 ] whereby they found down-regulation of complement C3 in subcutaneous tissue of obese women.…”
Section: Discussionsupporting
confidence: 94%
“…Plasma levels of these proteins are also excellent predictors of obesity, with PAI-1 being one of the top 5 circulating biochemical predictors of total, abdominal, visceral and liver fat 23 . Plasma PAI-1 activity is strongly correlated with elevated plasma triglyceride levels while plasma levels of complement protein 3a (C3a) increase with increasing level of obesity 24,25 . Given the separate association of coagulation and complement abnormalities with both adiposity and PGD after transplant, dysregulation of these pathways in thoracic VAT is an intriguing potential mechanism for the association of adiposity with PGD after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%